Longitudinal effects of race, ethnicity, and psychosocial disadvantage on systemic inflammation - Laura B. Zahodne; A. Zarina Kraal; Afsara Zaheed; Penelope Farris; Ketlyne Sol (Elsevier, 2019)
Objective: Psychosocial factors likely contribute to racial and ethnic inequalities in cardiovascular diseases (CVDs). However, precise social, psychological, and physiological pathways linking race and ethnicity to the development of CVDs are not well understood. Systemic inflammation, commonly indexed by C-reactive protein (CRP), is a biomarker for CVD risk and progression. The objective of this study was to identify mediating pathways from race and ethnicity to CRP through social, psychological, and behavioral variables. Methods: Using data from 12,382 participants aged 51 and older in the Health and Retirement Study, structural equation models tested for direct and indirect effects of race and ethnicity on CRP measured over four years through educational disadvantage, everyday discrimination, depressive symptoms, external locus of control, and smoking. Results: Educational disadvantage mediated Black-White and Hispanic-White disparities in baseline CRP directly, as well as indirectly through elevated depressive symptoms, higher external locus of control, and smoking. Educational disadvantage also mediated Black-White and Hispanic-White disparities in CRP change directly, as well as indirectly through higher external locus of control and smoking. Independent of education, discrimination mediated Black-White differences in baseline CRP via elevated depressive symptoms, higher external locus of control, and smoking. Discrimination also mediated Black-White disparities in CRP change via external locus of control. Conclusions: Results from this population-based, longitudinal study support the view that racially patterned social disadvantage is prospectively associated with longitudinal inflammatory processes, and some of these effects are independently mediated by psychological and behavioral factors. Biopsychosocial pathways to health disparities also differ between minority groups. Keywords: United States, Inflammation, Minority health, Discrimination, Education, Depression